A quantitative investigation of mathematical identity and its components in prospective mathematics teachers - Annisa Dwi Kurniawati; Muhammad Rizqi Saputra; Shofan Fiangga (Journal Focus Action of Research Mathematic (Factor M), 2025)
Mathematical identity has become a significant focus in mathematics education research because it influences how individuals perceive themselves as learners and practitioners of mathematics. Theoretical perspectives, including socio-cultural and discourse-based views, suggest that mathematical identity is constructed through personal experience, community recognition, and participation in mathematical practices. However, empirical research on the mathematical identity of prospective mathematics teachers remains limited, particularly studies that quantitatively examine the multiple components of identity before students enter the teaching profession. Addressing this gap, the present descriptive quantitative study investigates the mathematical identity of prospective mathematics teachers. A total of 88 participants completed the questionnaire on mathematical identity, which consisted of 18 items covering interest, recognition, competence, performance, and beliefs about mathematics. The responses were analyzed using descriptive statistical methods, including frequency distributions, mean scores, and categorical classifications. The results showed that 70.45% of prospective mathematics teacher students had a high mathematical identity. Component-level analysis revealed that 78.41% had high interest in mathematics, 55.68% had medium levels of recognition, 48.86% showed high competence beliefs, 92.04% scored high in performance beliefs, and 97.73% held strong positive beliefs about the nature of mathematics. This study contributes to the literature by providing a detailed quantitative profile of mathematical identity among prospective mathematics teachers. The findings suggest that teacher education programs should intentionally design learning environments that provide more opportunities for constructive feedback. Future research should examine the factors that shape and influence the development of mathematical identity, particularly through longitudinal or mixed-method approaches that can capture changes over time and provide deeper explanatory insights.